2006
DOI: 10.4141/s05-015
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen release during decomposition of crop residues under conventional and zero tillage

Abstract: . 2006. Nitrogen release during decomposition of crop residues under conventional and zero tillage. Can. J. Soil Sci. 86: 11-19. The litter-bag method was used in field experiments to determine nitrogen (N) loss patterns from decomposing red clover (Trifolium pratense) green manure (GM), field pea (Pisum sativum), canola (Brassica rapa) and monoculture wheat (Triticum aestivum) residues under conventional and zero tillage. Nitrogen contained in crop residues ranged from 10 kg ha -1 in wheat under both tillage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 39 publications
5
47
0
1
Order By: Relevance
“…Nitrate leaching, run-off, denitrification and microbial immobilization during spring thaw are all possible causes. Therefore, the rapid N mineralization by legume GM (Lupwayi et al 2006a) is not necessarily beneficial to the following crop, which is usually seeded more than 40 wk after GM residue placement. Winter wheat, which is seeded in the fall, or fall-seeded canola would probably make better use of nutrients released from crop residues than spring wheat or other crops that are seeded in spring of the following year.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrate leaching, run-off, denitrification and microbial immobilization during spring thaw are all possible causes. Therefore, the rapid N mineralization by legume GM (Lupwayi et al 2006a) is not necessarily beneficial to the following crop, which is usually seeded more than 40 wk after GM residue placement. Winter wheat, which is seeded in the fall, or fall-seeded canola would probably make better use of nutrients released from crop residues than spring wheat or other crops that are seeded in spring of the following year.…”
Section: Resultsmentioning
confidence: 99%
“…Because N fertilizer was applied to wheat (Table 1), these differences in N uptake under different residues are not necessarily related to N release from them, but past N fertilization history too. In the same trial, Lupwayi et al (2006a) reported that where net N release occurred, legume GM residues released 46 to 69 kg N ha -1 , peas 4 to 18 kg N ha -1 , canola 10 to 25 kg N ha -1 , and wheat 2 kg N ha -1 . Comparing these results with N uptake results under each crop residue (Table 4) indicates that N released from GM residues would meet up to 100% (100 × 69 kg ha -1 /69 kg ha -1 ) of wheat N requirements, but N released from pea, canola and wheat residues would meet only up to 19% (100 × 18 kg ha -1 / 93 kg ha -1 ), 27% (100 × 25 kg ha -1 / 92 kg ha -1 ) and 3% (100 × 2 kg ha -1 / 68 kg ha -1 ) of wheat N requirements.…”
Section: Wheat N Uptakementioning
confidence: 96%
See 1 more Smart Citation
“…All differences between treatments determined by single-degree-of-freedom contrasts (ns not significant) c Grouped treatments contrasted include wheat systems (WHT) = F-W, CW; legume systems (LEG) = LGM-W, P-W; low intensity systems (LI) = F-W, LGM-W; high intensity systems (HI) = CW, PW; fallow-wheat (F) = F-W; alternative to fallow-wheat (ALT) = CW, LGM-W, P-W. Values presented in grouped contrasts are differences between first and second treatment group our CW and P-W systems which likely returned higher quantities of ligninaceous residue fractions (Lupwayi et al 2006). In a similar but much longer-term study, Biederbeck et al (1994) and reported that a lentil (for grain)-wheat rotation had higher mineralizable C to 15 cm, higher mineralizable N in the 7.5-15 cm depth, and higher WAS to 5 cm relative to a F-W rotation, and that the lentil-wheat rotation often equaled effects of a CW rotation on these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…1). The High Intensity systems likely returned a relatively large fraction of ligninaceous and recalcitrant compounds to soils (Lupwayi et al 2006), thereby exhibiting depressed mineralization from SOM when N fertilizer is added. Our results also indicated that even though systems with legumes can have greater PMC and PMN than wheat-only systems, the mechanisms underlying why these fractions can accumulate-instead of rapidly decomposing and/or causing SOM priming-remain unclear.…”
Section: Discussionmentioning
confidence: 99%